A Complication of Nasotracheal Intubation After Mandibular Subcondylar Fracture - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2011)
Among the potential risks of nasotracheal intubation are nasal bleeding, sinusitis, bacteremia, accidental turbinectomy, and some other structural damages. Retropharyngeal dissection is reported as a very rare complication of nasotracheal intubation, mostly encountered in elective surgery patients. A case with traumatic subcondylar fracture of the mandible is presented here, which is suspected to be the cause of the nasopharyngeal dissection that was observed during attempted nasotracheal intubation.
Keywords: Nasotracheal intubation; retropharyngeal dissection; subcondylar fracture; mandible; RETROPHARYNGEAL DISSECTION; RARE COMPLICATION; TUBE; EPISTAXIS